Translocation of differently sized and charged polystyrene nanoparticles in in vitro intestinal cell models of increasing complexity. Issue 4 (May 2015) - Walczak, Agata P.; Kramer, Evelien; Hendriksen, Peter J. M.; Tromp, Peter; Helsper, Johannes P. F. G.; van der Zande, Meike; Rietjens, Ivonne M. C. M.; Bouwmeester, Hans
Abstract Intestinal translocation is a key factor for determining bioavailability of nanoparticles (NPs) after oral uptake. Therefore, we evaluated three in vitro intestinal cell models of increasing complexity which might affect the translocation of NPs: a mono-culture (Caco-2 cells), a co-culture with mucus secreting HT29-MTX cells and a tri-culture with M-cells. Cell models were exposed to well characterized differently sized (50 and 100 nm) and charged (neutral, positively and negatively) polystyrene NPs. In addition, two types of negatively charged NPs with different surface chemistries were used. Size strongly affected the translocation of NPs, ranging up to 7.8% for the 50 nm NPs and 0.8% for the 100 nm NPs. Surface charge of NPs affected the translocation, however, surface chemistry seems more important, as the two types of negatively charged 50 nm NPs had an over 30-fold difference in translocation. Compared with the Caco-2 mono-culture, presence of mucus significantly reduced the translocation of neutral 50 nm NPs, but significantly increased the translocation of one type of negatively charged NPs. Incorporation of M-cells shifted the translocation rates for both NPs closer to those in the mono-culture model. The relative pattern of NP translocation in all three models was similar, but the absolute amounts of translocated NPs differed per model. We conclude that for comparing the relative translocation of different NPs, using one intestinal model is sufficient. To choose the most representative model for risk assessment, in vivo experiments are now needed to determine the in vivo translocation rates of the used NPs.